2021
DOI: 10.3390/nano11102553
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer-Scale GaN/AlN Multiple Quantum Wells for High Power e-Beam Pumped UV-Emitters in the 240–270 nm Spectral Range

Abstract: Monolayer (ML)-scale GaN/AlN multiple quantum well (MQW) structures for electron-beam-pumped ultraviolet (UV) emitters are grown on c-sapphire substrates by using plasma-assisted molecular beam epitaxy under controllable metal-rich conditions, which provides the spiral growth of densely packed atomically smooth hillocks without metal droplets. These structures have ML-stepped terrace-like surface topology in the entire QW thickness range from 0.75–7 ML and absence of stress at the well thickness below 2 ML. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 68 publications
1
38
2
Order By: Relevance
“…In order to disregard the above‐mentioned issues, the electron beam‐pumped deep‐ultraviolet surface emitter (DUVSE) is proposed to increase the output power and avoid the conventional carrier injection layers. [ 22–28 ] The device merely consists of a carbon nanotube (CNT) field emitter and AlGaN multiple quantum wells (MQWs). This DUVSE announces plenty of advantages such as low emitted light re‐absorption, [ 24 ] simple epitaxial structure, [ 23 ] and solo‐device fabrication at wafer‐scale.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to disregard the above‐mentioned issues, the electron beam‐pumped deep‐ultraviolet surface emitter (DUVSE) is proposed to increase the output power and avoid the conventional carrier injection layers. [ 22–28 ] The device merely consists of a carbon nanotube (CNT) field emitter and AlGaN multiple quantum wells (MQWs). This DUVSE announces plenty of advantages such as low emitted light re‐absorption, [ 24 ] simple epitaxial structure, [ 23 ] and solo‐device fabrication at wafer‐scale.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have suggested that the utilization of AlGaN-delta-GaN MQWs or ultra-thin AlN/GaN MQWs is beneficial for mitigating QCSE, raising electron-hole wavefunction overlap, and accordingly increasing internal quantum efficiency (IQE). [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The performance of e-beam pumped light source and laser-based on these structures is also optimized. [24][25][26][27][28][29][30] Whereas, an over-thin QW structure at the monolayer (ML) level sometimes weakens carrier confinement capacity and contrarily decreases WPE.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last article of this Special Issue [ 7 ], the authors demonstrated the possibility of plasma-assisted molecular beam epitaxy to fabricate multiple GaN/AlN quantum wells (MQWs) with heterostructures that can be used in high-power ultraviolet (UV) emitters pumped by an electron beam. The main feature of these heterostructures, which can emit in the sub-250 nm UVC spectral range, is the ultra-thin quantum wells with a nominal thickness of less than 2 mL.…”
mentioning
confidence: 99%